Demographic Transition and an Ageing Society Implications for Local Labour Markets in Poland - Martinez-Fernandez, Cristina (OECD Publishing, 2013)
This report outlines the findings of the Poland case study for the combined study regions of Lódzkie, Malopolska and Pomorskie for the international project, Local scenarios of demographic change. The demographic situation is changing significantly within Poland with two major trends occurring, population decline and population ageing, as a result of decreasing fertility rates and increased life expectancy. However, the Polish case study revealed the complexity of demographic challenges with each region experiencing different issues associated with socio-economic context such as: population ageing experienced in all three study regions; and population shrinkage in Lódzkie. These differences in demographic situations require a territorial, local and regional strategy co-ordinated policy response with national policy efforts. Policy themes and recommendations focus on sustainable economic development, family policy, ageing workforce, silver economy, and skills and education
Keywords: Social Issues/Migration/Health; Urban, Rural and Regional Development; Industry and Services; Poland